THE ROLE OF POSITIVE EMOTION AS A MEDIATOR OF SHOPPING LIFESTYLE AND HEDONIC SHOPPING MOTIVATION TOWARDS IMPULSE BUYING AT TIKTOK SHOP (Case on TikTok Shop Customers) - Tatu Nur Ajizah; Arief Teguh Nugroho (Universitas Islam Lamongan, 2023)
Consumer impulsivity is one of the reasons for impulse purchases. A purchase decision made on the spur of the moment without prior forethought is called an impulse buy, and it can happen to consumers who shop physically as well as those who shop online or through social media. In the TikTok Store, this study intends to explore the function of positive emotion as a mediator of shopping habits and hedonic shopping motivation for impulsive purchases. A total of 138 respondents were included in the quantitative research model employed for this study. SmartPLS 3.2.9 data processing software was used to process the research, and a Google Form was used to collect the data. Purposive sampling is used with non-probability sampling in the sampling procedure. This study discovered that there is a direct and significant positive effect of shopping lifestyle on positive emotion in TikTok Shop customers, that there is no significant effect of hedonic shopping motivation on impulse buying in TikTok Shop customers, and that the role of positive emotion as a mediator of shopping lifestyle for impulse buying in TikTok Shop customers has no significant.